PENGARUH PEMBERIAN OX-LDL TERHADAP AKTIVASI NF-кB DAN PPARγ γγ γSERTA APOPTOSIS PADA KULTUR HUVEC’s - Riawan, Wibi; Wibowati, Samodijanti (Jurnal Kedokteran Brawijaya, 2006)
Oxidized LDL (ox-LDL) causes activation and dysfunction of endothelial cells through NFκB activation after binding process of ox-LDL to LOX-1. One of ox-LDL components had been known as the activator of PPARγ. This study was done to see the effect of ox-LDL on NFκB and PPARγactivation and apoptosis of HUVEC’s culture. HUVEC’s culture was divided into 3 groups : control (without any treatment) and 2 groups which were treated with ox-LDL 25ug/mL and 50ug/mL. Activation of NFκB and PPARγwere determined by immunodoublestaining using mouse monoclonal anti NFκB and mouse monoclonal anti PPARγafter 30 minutes exposure of ox-LDL. The expression of TNFαand apoptotic cell were determined by immunodoublestaining using  TUNEL fragmented DNA labeling and goat polyclonal anti human TNFαafter 24 hours exposure of ox-LDL. HUVECs culture that had been treated with 25  µg/ml and 50µg/ml of ox-LDL, showing activation of NFκB but not PPARγ. This treated endotel showed apoptotic characteristic which had conformed with DNA fragmented. These cells also showed the increase of TNFαexpression on the cytoplasm. Ox-LDL could increase translocation of NFκB gen transcription to nucleus followed by the increase of TNFαthat can cause apoptotic of the cells. Key words: ox - LDL, Endothel, NF-κB, PPARγ, Apoptosis